Technological competition and patent strategy: Protecting innovation, preempting rivals and defending the freedom to operate - Cappelli, Riccardo; Corsino, Marco; Laursen, Keld; Torrisi, Salvatore (Research Policy, 2023)
Drawing on the resource-based view of the firm, we examine the effect of technological competition over a patent on the firm's choice of patenting strategy. We claim that technological competition makes the traditional strategy of protecting focal innovations from imitation less likely and increases the likelihood of a play strategy — i.e. using patents to avoid the risk of hold-up by other patent owners, or as a bargaining chip in litigation and cross-licensing. However, we claim also that technological competition over a target close to the firm's core technology should lead to use of a fence strategy i.e. to blocking the commercial endeavors of rivals and preempting substitute inventions. We find support for our hypotheses using data from a large-scale survey of European patent applications.